Blended learning for postgraduates; an interactive experience - Mirjam Westerlaken; Ingrid Christiaans-Dingelhoff; Renée M. Filius; Bas de Vries; Martine de Bruijne; Marjel van Dam (BMC Medical Education, 2019)
Abstract Background Blended learning has the potential to stimulate effective learning and to facilitate high quality education. For postgraduate health professionals, blended learning is relatively new. For this group we developed, implemented and evaluated two blended learning modules in a master program on quality and safety in patient care. Aiming for a better preparation compared to traditional textbook homework, the course provided not only web lectures and reading, but also interactive assignments and collaborative learning. Additional goal was saving time for the teachers resulting in a potential cost savings. Method The experiences of 21 postgraduate health professionals were evaluated with two voluntary and anonymous questionnaires beginning of 2017 with a special focus on the added value of online interaction, underexposed in previous research. Results This evaluation shows that online modules are regarded as being an effective preparation for face-to-face meetings for postgraduate health professionals. Added value of social interactive online preparation was perceived from collaborating and interacting with each other. Both the interaction between the students, and the e-moderator and teachers were well received. Conclusions Based on the results of this study, we suggest that blended learning may indeed increase the level of education and stimulate effective learning for postgraduate health care professionals. The professionals experienced added value of social interactive online preparation from collaborating and interacting with each other. We consider better aligning of the online and face-to-face components as one of the highest priorities.